Existence result for fractional Schrödinger–Poisson systems involving a Bessel operator without Ambrosetti–Rabinowitz condition. (1st January 2018) - Shen, Liejun
Abstract: The present study is concerned with the nontrivial solutions for fractional Schrödinger–Poisson system with the Bessel operator. Under certain assumptions on the nonlinearity f, a nontrivial nonnegative solution is obtained by perturbation method for the given problem. In particular, the Ambrosetti–Rabinowitz type condition or the monotone assumption on the nonlinearity is unnecessary.